The Relationship Between Maximum Lower Limb Strength & Power, and GPS Acceleration Speed in Elite U20 Gaelic Football Athletes - Michael O'Driscoll; Tommy Mooney; Liam Sweeney (International Universities Strength and Conditioning Association, 2024)
Previous research indicates positive relationships between high levels of lower limb strength and power, and acceleration sprint velocity in team sport athletes. This cross-sectional study aimed to investigate the relationship between lower limb absolute and relative strength, countermovement jump (CMJ) height, and Global Positioning System (GPS) recorded 20m acceleration sprint velocity in elite male U-20 Gaelic football athletes. Nineteen athletes (19.0 ± 0.5 years; 81.1 ± 5.5 kg; 182 ± 6.2 cm) from the same elite U-20 squad participated in this study during an in-season period. Subjects performed a >95% 1RM box squat, a 20m sprint test, and a CMJ test. Relative maximum lower limb strength (r = 0.54, 95% CI [0.11 to 0.8]; p < 0.05) and CMJ height (r = 0.66, 95% CI [0.29 to 0.86]; p < 0.001) showed strong correlations with 20m sprint velocity. A multiple linear regression analysis demonstrated that lower limb maximum relative strength and CMJ height significantly predicted 20m sprint velocity (Adjusted R2 = 0.51, F (2, 16) = 6.29, p < 0.05). These findings provide evidence for the importance of elite under-age Gaelic football athletes acquiring high levels of lower limb strength and power characteristics to enhance acceleration sprint performance.